الترويج الابتكاري كآلية حديثة للنهوض بالصناعة السياحية - شين، الخثير; مشتر، فطيمة Meshter, Fatimah (المركز الجامعي المقاوم الشيخ آمود بن مختار إيليزي, 2020)
تعتبر صناعة السياحة من أهم الصناعات الحديثة وأسرعها تطورا، والتي بإمكانها تحقيق مداخيل تفوق قيمتها ما تحققه الصناعات الأخر ى، وأمام اشتداد المنافسة كان لزاما على الدول التي تملك مقومات سياحية إدخال مفاهيم جديدة للنهوض بالنشاط السياحي إلى المستوى المرضي، أهم هذه المفاهيم الابتكار خاصة في مجال الترويج للمنتج السياحي عبر مختلف الوسائل، وهذا ما سنحاول التطرق إليه من خلال دراستنا الموسومة بعنوان: '' الترويج الابتكاري كآلية حديثة للنهوض بالصناعة السياحية''، حيث سنتطرق إلى مفهوم الترويج السياحي محاولين إبراز دوره في التنشيط السياحي والنهوض بالصناعة السياحية واخترنا بعض التقنيات المبتكرة كنموذج للتحليل مختتمين الدراسة باقتراحات وتوصيات يمكن تطبيقها على مستوى الجزائر.
Tourism industry is considered one of the most important and fastest developing modern industries, which can achieve incomes that exceed its value compared to other industries. As the competition intensifies, it was obligatory for countries that possess tourism ingredients to introduce new concepts to advance tourism activity to the satisfactory level. The most important of these concepts of innovation, especially in the field of promoting tourism product through various means, and this is what we will try to address through our study labeled: `` Innovative promotion as a modern mechanism for the advancement of the tourism industry '', where we will address the concept of tourism promotion, trying to highlight its role in tourism activation and the advancement of the tourism industry and we chose some innovative technologies as a model for the analysis. We concluded the study with suggestions and recommendations that can be applied at the Algerian level.
Keywords: الابتكار الترويجي -- التسويق السياحي -- المزايا التنافسية -- المؤسسات الجزائرية